Effects of hormone-primed oviduct epithelial cell co-culture system on swine SCNT embryo development - Chen, Zhong-Ping; Wang, Jian; Bian, Chang-Di; Wang, Dong-Yue; Feng, De-Hui; Wei, Ming-Yi; Yu, Da-Wei; Sun, Wei-Jun; Zhang, Lin-Lin (Frontiers in Cell and Developmental Biology, 2025)
The developmental efficiency of swine somatic cell nuclear transfer (SCNT) embryos remains limited, primarily due to the lack of physiologically relevant in vitro culture conditions that can fully support reprogramming and early embryogenesis. In this study, we established a co-culture system using swine oviduct epithelial cells (OECs), including untreated and hormone-pretreated OECs with estradiol and progesterone (EP-OECs), to better mimic the oviductal environment. Compared with the control group, EP-OECs exhibited elevated expression of the oviduct-specific marker OVGP1. Moreover, SCNT embryos co-cultured with EP-OECs displayed a significantly higher blastocyst formation rate (control: 18.6% ± 0.01; OEC: 24.5% ± 0.01; EP-OEC: 30.5% ± 0.03). Although the total blastocyst cell number did not increase, co-culture significantly elevated intracellular glutathione (GSH) levels and reduced oxidative stress at key developmental stages. Single-cell transcriptomics (SMART-seq2) analysis revealed that the co-culture activated multiple metabolic pathways, including the pentose phosphate pathway and lipid metabolism, thereby improving redox regulation and energy utilization. Moreover, embryonic development was enhanced through the modulation pluripotency-associated factors, including SOX2, and activation of the PI3K–AKT signaling cascade. Notably, OEC co-culture induced PI3K upregulation at the 8-cell stage and further affected PDK expression. OEC/EP-OEC co-culture treatment suggests PI3K-AKT signaling pathway activation in embryos, which may be a key mechanism promoting embryonic development. These findings indicate that hormone-primed OEC co-culture provides a microenvironment that closely resembles in vivo conditions, offering an effective strategy for improving the efficiency of swine cloning and a new insight into the molecular mechanisms underlying embryonic development in vitro.